Preparation of CdIn2Se4n-type semiconductor used as thermoelectric material by solgel method - Aun Anong Ruanthon (2018)
The objective of this research was to study the effect of various parameters such as temperature and pH to the formation of cadmium indium selenide (CdIn2Se4) thin films, which were fabricated by solgel dip-coating method. This n-type semiconductor compound is suitable for application as thermoelectric materials. Cadmium, indium, selenium precursors were separately dissolved by solvents: ethanol, hydrochloric acid, and acetic acid to form metal alkoxides. The precursor solutions were then mixed together in N2atmosphere. These metal alkoxides were hydrolyzed by adding water and then polycondensed by adding ethylene glycol to become gels. These gels were adjusted to various acid-base values by adding diethylnolamine. Glass substrates were dipped into the gels to form thin films. These thin films were annealed at various temperatures in N2atmosphere and characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and fourier transfrom infrared spectroscopy (FTIR) techniques. The results indicated that CdIn2Se4compound occurred by the reaction at room temperature with pH 4 and annealed at 450°C in N2atmosphere. © 2009 World Scientific Publishing Company.